2011
DOI: 10.1080/14786435.2010.488636
|View full text |Cite
|
Sign up to set email alerts
|

Continuum crystal plasticity analyses of the plastic flow features underneath single-crystal indentations

Abstract: Continuum crystal plasticity finite element simulations are performed for archetypal pure and alloyed fcc crystals to investigate the role of the crystalline orientation, hardening response and dislocation interactions on the plastic flow patterns developing underneath spherical and pyramidal\ud indenter tips. Following our prior analyses, the orientation of plastic features such as subsurface lobes and surface rosettes goes along that of specific in-plane and out-of-plane slip systems. Interestingly, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…A reduction of sinking-in or an enhancement of pileup effects with increasing penetration is thus found to occur concurrently with an intensification in the outwards spreading of the plastic zone at the indented surface. Consequently, the plastic zone shape only remains constant in the strict limiting cases of rigid-perfectly-plastic and rigid-power-law hardening material responses, so that geometrical-similarity is again violated in solids with a marked r ys (Mata et al, 2006;Alcalá et al, 2010).…”
Section: Deconstructing Self-similaritymentioning
confidence: 97%
“…A reduction of sinking-in or an enhancement of pileup effects with increasing penetration is thus found to occur concurrently with an intensification in the outwards spreading of the plastic zone at the indented surface. Consequently, the plastic zone shape only remains constant in the strict limiting cases of rigid-perfectly-plastic and rigid-power-law hardening material responses, so that geometrical-similarity is again violated in solids with a marked r ys (Mata et al, 2006;Alcalá et al, 2010).…”
Section: Deconstructing Self-similaritymentioning
confidence: 97%
“…In this work the stresses, shear strains, and crystal lattice rotation map within the material were obtained and the numerical predictions were validated with the experimental results (nanoindentation tests and EBSD investigation of the indented area). Moreover, both spherical and pyramidal indentation tests in fcc single crystals were simulated by Alcala et al [10] and Narayanan et al [11] Zahedi et al [12] developed their own crystal plasticity models to investigate spherical indentation in copper single crystals. Not only Cu but also single crystals made of other materials have been investigated recently.…”
Section: Nanoindentation Is a Technique Which Hasmentioning
confidence: 99%
“…This is due to the asymmetry of the Berkovich indenter, as discussed before, and differences between the size of plastic zones at both flanks were observed also by other authors 300 . Apart from this asymmetry, Alcalá et al 340,341 found that plastic zones for Berkovich indentations do not differ much from those produced by spherical indenters. Thus, the growth direction of martensite under the nanoindenter can be considered as the result of shear stresses on multiple slip systems activated by nanoindentation.…”
Section: Small <001> Oriented Grainsmentioning
confidence: 96%
“…Alcalá et al 340,341 performed analyses of the plastic behavior below nanoindentations in Cu. Their results are represented in Figure 95, where the simulation shows that for fcc materials plastic flow is favored parallel to the indentation axis for <111> oriented grains, while for <001> grains it is flattened in vertical direction, but prolonged parallel to the surface plane.…”
Section: Small <001> Oriented Grainsmentioning
confidence: 99%
See 1 more Smart Citation